Economic Growth or Regress – Scenarios and Bibliometric Analysis on Single Taxation vs. Progressive Taxation - Ramona-Ionela Haraguș; Attila Szora Tamaș; Gabriel Szora Tamaș (Revista de Studii Financiare, 2023)
The discussion on single taxation vs. progressive taxation returns periodically and always in times of budgetary crisis, which in turn induces the economic crisis and not the other way around, as normal. The purpose of this article is to observe the evolution of taxation in progressive tax rates compared to taxation in single rates in Romania, but also in other European countries. The research methodology involved the qualitative analysis of the various scenarios, already existing at national and international level on the single taxation vs. progressive taxation, as well as documentation by quantitative analysis of the focus of literature on the evolution of taxation in progressive quotas. Following the analysis, it was found that the tax system in progressive quotas existing in Romania until 2004 generated a low level of revenues to the budge. In many European countries, however, a progressive taxation system is applied, which reinforces the OECD’s assertion that there is no tax system „unique to all”.